Spatial Distribution, Contamination Levels, and Ecological Risk of Total Mercury and Methyl Mercury in the Gulf of Guinea Sediments - Lailah Gifty Akita; Samuel Olatunde Popoola; Marcel Konan Yao; Lazare Kouame Akpetou; N.’goranJean-Paul Yao; Edmond Sossoukpe; Ehoumi Paul Sossou; Joseph Nkwoji; Benjamin O. Botwe; Andrews Agyekumhene; Francis E. K. Nunoo; Elvis Nyarko; et al. (Water, Air, & Soil Pollution, 2026)

Heavy metal contamination in surface sediment and seafood from the Pra Estuary (Ghana): an ecological and human health risk assessment - Benjamin O. Botwe (Ecotoxicology, 2026)

Perspectives from Developers and Users of the GOA-ON in a Box Kit: A Model for Capacity Sharing in Ocean Sciences - Alexis Valauri-Orton, Valauri-Orton; Kaitlyn Lowder; Kim Currie; Christopher Sabine; Andrew Dickson; Sophie Chu; Alberto Acosta; Francis Asuquo; Rafael Bermudez; Ulrich Bilounga; Kishore Boodhoo; Benjamin Botwe; et al. (Oceanography, 2025)
Providing reliable instrumentation that enables collection of high-​quality, comparable data is one of the most challenging aspects of establishing ocean acidification monitoring programs. This is especially true for under-resourced countries, where such data are mostly unavailable. In 2016, The Ocean Foundation (TOF) worked with international bodies, including the International Atomic Energy Agency’s Ocean Acidification International Coordination Centre and the Global Ocean Acidification Observing Network (GOA-ON), and subject matter experts to develop a set of equipment known as the “GOA-ON in a Box” kit (The Ocean Foundation, 2017). This comprehensive kit provides researchers with everything needed—down to specialized rubber bands—to obtain weather-quality carbonate system measurements as defined by GOA-ON (Newton et al., 2015). Data are generated from spectrophotometric measurements of pHT and manual titrations for total alkalinity from discrete samples as well as in situ sensors, the iSAMI-pH and a CTD. The kit’s modular design, composed of nearly 100 unique items, makes it much less expensive than comparable integrated systems and allows for easier troubleshooting and replacement of supplied spare components.

Assessment of coastal and marine ecosystems in West Africa: The case of Ghana - Richard Takyi; Badr El Mahrad; Cynthia Addo; John Essandoh; Mohamed ElHadary; Richard Adade; Eddiebright Joseph Buadi; Benjamin Osei Botwe; Francis Kofi Ewusie Nunoo (Marine Pollution Bulletin, 2023)

Total coliforms, arsenic and cadmium exposure through drinking water in the Western Region of Ghana: application of multivariate statistical technique to groundwater quality - Andrews Obeng Affum; Shiloh Dede Osae; Benjamin Jabez Botwe Nyarko; Samuel Afful; Joseph Richmond Fianko; Tetteh Thomas Akiti; Dickson Adomako; Samuel Osafo Acquaah; Micheal Dorleku; Emmanuel Antoh; Felix Barnes; Enoch Acheampong Affum (Environmental Monitoring and Assessment, 2015)